2016
DOI: 10.1097/yic.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

A thorough QT study to evaluate the QTc prolongation potential of two neuropsychiatric drugs, quetiapine and escitalopram, in healthy volunteers

Abstract: Prolongation of the QT interval on an ECG is a surrogate marker for predicting the proarrhythmic potential of a drug under development. The aim of this study was to evaluate the QTc prolongation potential of two neuropsychiatric drugs, quetiapine immediate release (IR) and escitalopram, in healthy individuals. This was a randomized, open-label, 4×4 Williams crossover study, with four single-dose treatments [placebo, 400 mg moxifloxacin (positive control), 20 mg escitalopram, and 100 mg quetiapine IR], conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…The risk of QT prolongation and torsade de pointes following escitalopram administration and the reported dose–response relationship with QT prolongation has raised concerns, with escitalopram dosage limitations from the European medicines agency and the UK medicines and healthcare products regulatory agency, but not from the Food and Drug Administration . Taking into account the large between‐subject variability in escitalopram exposure, the modest influence of CYP2C19 inhibitors is not expected to put patients at increased risk of QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of QT prolongation and torsade de pointes following escitalopram administration and the reported dose–response relationship with QT prolongation has raised concerns, with escitalopram dosage limitations from the European medicines agency and the UK medicines and healthcare products regulatory agency, but not from the Food and Drug Administration . Taking into account the large between‐subject variability in escitalopram exposure, the modest influence of CYP2C19 inhibitors is not expected to put patients at increased risk of QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of QT prolongation and torsade de pointes following escitalopram administration and the reported dose-response relationship with QT prolongation has raised concerns, [55][56][57] with escitalopram dosage limitations from the European medicines agency and the UK medicines and healthcare products regulatory agency, but not from the Food and Drug Administration. [58][59][60] Taking into account the large A recently published study demonstrated that clinicians tend to overestimate the impact of the inhibitory effect of ritonavir/cobicistat, resulting in the use of too low doses of psychotropic drugs in PLWH due to fear of DDIs.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology is not clear. Methadone metabolites [3], interaction with other medications that cause Q-T prolongation (e.g., antibiotics and atypical antipsychotics) [4,5], hepatic dysfunction and electrolytes abnormalities [6] are potential mechanisms. Although our patient's medications include Quetiapine which is an atypical antipsychotic that is known to cause Q-T prolongation, he was on this medication for many years and his baseline Q-T was 459 milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten mit Altersdepression wären solche direkten Vergleichsstudien, insbesondere auch in Hinblick auf die Erhaltungstherapie, wünschenswert. Bezüglich der Verträglichkeit sollte das Nebenwirkungsprofil der Antipsychotika beachtet werden, welches häufig den Einsatz einschränkt: neben den oben genannten Nebenwirkungen unter Aripiprazol zeigt sich bei älteren Menschen insbesondere unter Quetipain häufig eine Sedierung, Schwindel, QTc-Zeit-Verlängerungen und auch orthostatische Dysregulationen [37] -Nebenwirkungen, die unter Lithium seltener auftreten.…”
Section: Alternative Strategien Bei Therapieresistenzunclassified